Effects of the Chemical and Mechanical Pre-Treatment of Brown Seaweed on Biomethane Yields in a Batch Configuration - Ashleen Marshall; Oluwaseun Oyekola (Biomass)
Brown seaweed could be a viable option for biogas production, with the added advantage of not competing with land-based crops, which negates the food vs. fuel argument. To optimise the process, this research investigates using mechanical and chemical pre-treatment to increase the biomethane yield of seaweed. The biomethane potential, biodegradability index, and biomethane yields were determined as well as the kinetics based on the hydrolysis of the anaerobic digestion process. Mechanical pre-treatment showed the highest increase in methane yield for the smaller size (<1.7 mm), recording yields of 126.16 mL/g VS after 28 days when compared to 31.54 mL/g VS for the control (2–3 mm). Chemical pre-treatment yielded higher methane rates (34.59–60.33 mL/g VS) than the control, but not as high as the mechanical pre-treatment processes. First-order kinetics described the anaerobic digestion process, with k-values between 0.050 and 0.106. The biodegradability index was between 0.145 and 0.580. The research increased the knowledge base of the potential of the Ecklonia Maxima seaweed to produce biogas. Careful consideration of the impact on the overall process must be completed to determine the advantages or disadvantages of including a pre-treatment step in the process under consideration.